Pioneer re-entry into covered stent graft to recanalize occluded, jailed external iliac artery - Ryan Gedney, MD; Mathew Wooster, MD, MBA (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Aortoiliac occlusive disease in patients who are poor surgical candidates requires innovative strategies in endovascular surgery. We present a case of a 59-year-old gentleman with significant medical comorbidities and chronic limb-threatening ischemia secondary to a chronically occluded left-to-right cross-femoral bypass, as well as an occluded right iliac system owing to a jailed right external iliac artery from a prior common-to-internal iliac covered stent, originally done for buttock claudication. He was treated successfully from an endovascular approach with kissing stents in the right internal and external iliac arteries after gaining access to the old right common iliac stent via an ipsilateral access and use of a Pioneer intravascular ultrasound-guided re-entry catheter. Use of this strategy to treat complex aortoiliac occlusions in patients that are not suitable surgical candidates can be achieved effectively, even in the setting of existing prior ipsilateral stent grafts.